Yes! Kissing Too… The Child Would Not Be Hurt in Any Way: Social Constructions of Child Sexual Abuse in the Ga Community in Ghana - Markwei, Ummu (Qualitative Sociology Review, 2019)
The United Nations Convention on the Rights of the Child obligates nations to protect children from all forms of abuse including sexual. However, child sexual abuse is a complex phenomenon which is difficult to understand as a result of cultural reasons. In view of this, the programs, policies, and interventions put in place to curb the phenomenon of child sexual abuse globally can only be effective if they are relevant to the social and cultural setting within which it happens. This is an exploratory study that sought to investigate social constructions of child sexual abuse in the Ga community. The study uses qualitative research methods to collect data from 42 respondents via six focus group discussions across three selected towns in the Greater Accra Region of Ghana. The findings showed that sexual activities between adults and children that were regarded as acceptable did not constitute child sexual abuse. However, sexual behaviors between adults and children that were regarded as unacceptable were viewed as serious, hence, considered as sexual abuse. The findings of this study illustrate the need for appropriate cultural interventions in curbing the phenomenon of child sexual abuse in the Ga Community in Ghana.